Natural convective flow in circular and arc cavities filled with water-cu nanofluid: a comparative study (Journal of Naval Architecture and Marine Engineering, 2018)
The fluid flow and heat transfer mechanism on steady state solutions obtained in circular and arc-square enclosures filled with water/Cu nanofluid as well as base fluid has been investigated numerically by Galerkin's weighted residual finite element procedure. The left and right boundaries of the cavities are, respectively, heated and cooled at constant temperatures, while their horizontal walls are adiabatic. Effects of buoyancy force (Rayleigh number) and viscous force (Prandtl number) with a wide range of Ra (103 - 106) and Pr (4.2 - 6.2) on heat transfer phenomenon inside cavities are observed. The fluid flow and temperature gradient are shown by streamlines and isotherms patterns. From the investigation, it is reported that the Rayleigh and Prandtl numbers are playing significant role in heat transfer rate. The variation in heat transfer is calculated in terms of average Nusselt number. Heat transfer rate is found to be higher for water/Cu nanofluid with 2% solid volume fraction than pure water. About 2.7% higher heat transfer rate is obtained for circular cavity than that of arc cavity using water/Cu nanofluid at Ra = 104 and Pr = 5.8.